Clinical Analyses of Efficiency of Multicomponental, Vitreoretinal Surgery of Eye Trauma - A.-G. D. Aliev; A. A.-G. Aliev; A. B. Abdulaev; M. M. Nurudinov (Oftalʹmologiâ)
Eye trauma is one of the leading causes of blindness and low vision in young working age people. It gives this particular group of diseases a special social significance. The absence of a universal surgical treating tactic is explained by the variety of traumatic agents and the various types of injuries. Penetrating wounds with the introduction of a foreign body, accompanied by detachment of the retina, vascular membrane, hemorrhagic and infectious complications are the most difficult in the clinical plan.Material and methods: 103 with penetrating eye injuries were operated during the period from 2015 to 2017. 29 of them were involving the introduction of foreign bodies, which were removed at different times: 18 eyes (62 %) — at 7–10 days, 8 eyes 27.5 %) — 14–28 days after injury and 3 eyes (10.3 %) — more than 1 month. In all cases, subtotal vitrectomy 25G (68.9 %) was performed, in some cases, 23-hedge vitrectomy was preferred (31 %) due to pronounced fibro-proliferative changes in the vitreous body. In the case of a foreign body impacted into the shells with dimensions greater than 4 mm, the real cavity was tamped with PFOS.Results. The adherence of the detached retina was achieved in 14 cases, adherence of the choroid — 4 cases. Uveitis was observed in 5 cases, ophthalmic hypertension in 12 patients in the early postoperative period. Hypertension was compensated by using the antihypertensive regimen. 5 patients at the time of hospitalization had a Vis = 0, the operation was of a diaphragm-preserving nature, since a foreign body that was not removed was the cause of the development of subatrophy of the eyeball in 16 % of cases. The remaining patients had stable, positive dynamics of visual functions in the postoperative period.Conclusion: Surgery tactics for extensive eye injuries are individual, and the amount of intervention depends largely on the parameters of the traumatic agent, so planned surgery is preferable to emergency because it allows for detailed preoperative examination and to get valuable information about the condition of the eye. The exceptions are injuries with symptoms of acute endophthalmitis. Multi-unit operations provide optimal conditions for the preservation of the eye as an organ and contribute to the restoration of visual functions.